Human reproductive and prenatal genetics - Leung, Peter C. K., (Ed.); Qiao, Jie, (Ed.) (London ; San Diego, CA : Academic Press, an imprint of Elsevier, 2019)
Human Reproductive and Prenatal Genetics presents the latest material from a detailed molecular, cellular and translational perspective. Considering its timeliness and potential international impact, this all-inclusive and authoritative work is ideal for researchers, students, and clinicians worldwide. Currently, there are no comprehensive books covering the field of human reproductive and prenatal genetics. As such, this book aims to be among the largest and most useful references available.--
Biological Significance of the Translation Program in OocytesConclusions and Perspectives; Chapter 10: Translational Regulation of Gene Expression During Oogenesis and Preimplantation Embryo Development; Abstract; Introduction; Factors Determining Oocyte Transcriptome; Essential Regulatory Components of Translation in Somatic Cells; Translation Regulatory Pathways in Oocytes and Early Preimplantation Embryos; Translational Regulation in the Early Embryo; Conclusion; Chapter 11: MicroRNAs in Gametes and Preimplantation Embryos: Clinical Implications; Abstract; Acknowledgments; Introduction
Includes bibliographical references and index.
Keywords: Human reproduction; Human reproductive technology; Medical genetics; Reproduction; Human Genetics; Genetics, Medical; Medical genetics; Human reproductive technology; Human reproduction